Memahami Makna Hadis Secara Tekstual dan Kontekstual - Liliek Channa AW (Universitas Islam Negeri Mataram, 2011)
Understanding hadîts is a daunting task because hadîts is everything ascribed by Prophet Muhammad saw. his utterances, deeds, and his provisions in his status as the Messenger of Allah and imitating Prophet Muhammad saw. is the manifestation of noble consensus. Muhammad saw. is the final prophet and his provisions should prevail endlessly, although he lived temporarily. Thus understanding hadîts, should not merely be done by textual approach if we want hadis to prevail for all time, considering the problems of life nowadays are getting more and more complex. Thus we need contextual approach, which is understanding hadîts or sunnah in accordance with the background, situation, condition, and the position of Prophet Muhammad in which the hadis or sunnah is ascribed.